Antiglycation and antioxidant potential of novel imidazo[4,5-b]pyridine benzohydrazones - Muhammad Taha; Khaled A.A. Alkadi; Nor Hadiani Ismail; Syahrul Imran; Aishah Adam; Syed Muhammad Kashif; Syed Adnan Ali Shah; Waqas Jamil; Salman Sidiqqui; Khalid Mohammed Khan (Arabian Journal of Chemistry, 2019)
A series consisting of 30 novel imidazo[4,5-b]pyridine benzohydrazones have been synthesized and evaluated for their antiglycation activity as well as their antioxidative potential. The synthetic part involves a 3-step reaction in which a pyridine diamine was being converted into a imidazo[4,5-b]pyridine, which was then subjected through another reaction to yield benzohydrazide. Subsequently, the attained benzohydrazide of imidazo[4,5-b]pyridine was used to synthesize the target molecules after treating them with the appropriate benzohydrazone derivatives. The derivatives were evaluated for the antiglycation and antioxidant activities. Result obtained showed that di and trihydroxy substituted compounds showed good activity with compound 25 (140.16 ± 0.36 μM) having the most potent antiglycation activity, which is twice lower than Rutin. The results also showed certain correlation between antiglycation activities with DPPH radical scavenging model as well as FRAP which indicated the participation of antioxidative effect in inhibiting glycation activity. Keywords: Imidazo[4,5-b]pyridine, Benzohydrazone, Antiglycation, Antioxidant